Effectiveness of targeting fathers for breastfeeding promotion: systematic review and meta-analysis - Pasyodun Koralage Buddhika Mahesh; Moraendage Wasantha Gunathunga; Suriyakumara Mahendra Arnold; Chintha Jayasinghe; Sisira Pathirana; Mohamed Fahmy Makarim; Pradeep Malaka Manawadu; Sameera Jayan Senanayake (BMC, 2018)
Abstract Background Further research gaps exist in relation to the promotion of breastfeeding. Robust scientific evidence obtained by a meta-analysis would provide objectively summarized data while enabling the assessment of consistency of findings. This review includes the first documented meta-analysis done on the effectiveness of targeting fathers for promoting breastfeeding (BF). Assessments have been done for a primary outcome and for six more secondary outcomes. Methods PubMed, EMBASE, Google Scholar, CENTRAL databases and unpublished researches were searched. Selections of randomized-controlled trials and quasi-experimental studies were done in three rounds. Heterogeneity and potential publication bias were assessed. Eight studies were included in meta-analysis and others in narrative synthesis of the outcomes. Pooling was done with the Mental- Haenszel method using risk ratio (RR). Summary-of-Findings table was composed by Review-Manager (version 5.3) and GRADEproGDT applications. Subsequent sensitivity analysis was done. Results Selected eight interventional studies included 1852 families. Exclusive BF at six months was significantly higher (RR = 2.04, CI = 1.58-2.65) in the intervention groups. The RR at 4 months was 1.52 (CI = 1.14 to 2.03). Risk of full-formula-feeding (RR = 0.69, CI = 0.52-0.93) and the occurrence of lactation-related problems were lower in the intervention groups (RR = 0.24, CI = 0.10-0.57). More likelihood of rendering support in BF-related issues was seen in intervention groups (RR = 1.43, CI = 1.22-1.68). Increase of maternal knowledge and favorable attitudes on BF were higher in the intervention groups (P ≤; 0.001). The quality of evidence according to GRADE was "low" (for one outcome), "moderate" (for four outcomes), and "high" (for two outcomes). Conclusions Targeting fathers in promotion of BF has provided favorable results for all seven outcomes with satisfactory quality of evidence. This review was registered in the PROSPERO-registry (ID: 2017-CRD42017076163) prior to its commencement.